La Biodanza como mediador socio emocional en niños de 5 a 6 años de la Institución Educativa San Vicente Ferrer Antioquia - Alzate Ramírez, Yeniffer (Educación, Ciencias Humanas y Sociales, 2018)
With this work we develop an analysis on Biodanza as a socioemotional mediator in children from ages five to six within San Vicente Ferrer Academic Institution through the planning and execution of research work that allowed the application of the mentioned discipline, thanks to the positive results obtained its relevance is recognized and validates a more widespread use on academic environments. The proposal developed is focused on hermeneutics as a methodological approach which allows the interpretation of the results obtained on semi-structured interviews as well as documented real life experiences. Parallel to this a reflection and critical study are carried out based on the direct and indirect interaction amongst the participating children while the reflective workshops are taking place.